A neo-feudal world order? Introduction to the symposium on Peter Hägel's Billionaires in World Politics. Issue 2 (4th May 2022) - Culp, Julian
ABSTRACT: The central aim of Peter Hägel's Billionaires in World Politics ( BWP ) is to challenge the assumption that private individuals lack agency and power in world politics – an assumption that is widely shared in the field of International Relations (IR). Hägel's methodological strategy to achieve this aim is twofold. First, he concentrates on minutest biographical aspects of billionaires to lay bare the idiosyncrasy of their choices, and to falsify, thus, structuralist assumptions of how individual agency is undermined by factors such as class, roles, or fields. Second, Hägel engages in counter-factual reasoning to support the claim that these individual decisions end up having a real impact on public affairs abroad. This impact is difficult to overestimate given that, as Hägel reveals, billionaires have affected a whole array of political issues, including Brexit, climate change policy, democratic development in Eastern Europe, global health policy, the Israeli-Palestine conflict, and the war in Iraq. This introduction starts off by elaborating on the central scholarly contribution of BWP . Following that, this introduction explains why the insights that BWP provides suggest that we do not live in a neo-feudal order, despite the immense global economic inequality which billionaires' wealth manifests.